2018
DOI: 10.1063/1.5008490
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pore geometry on the compressibility of a confined simple fluid

Abstract: Fluids confined in nanopores exhibit properties different from the properties of the same fluids in bulk; among these properties is the isothermal compressibility or elastic modulus. The modulus of a fluid in nanopores can be extracted from ultrasonic experiments or calculated from molecular simulations. Using Monte Carlo simulations in the grand canonical ensemble, we calculated the modulus for liquid argon at its normal boiling point (87.3 K) adsorbed in model silica pores of two different morphologies and v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(90 citation statements)
references
References 58 publications
8
82
0
Order By: Relevance
“…The internal pore diameters used in DBdB equations were recalculated from the external diameters in the range of 2-10 nm, the difference is explained in details in Ref. 48. A comparison of the isotherms is shown in Figure 2.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…The internal pore diameters used in DBdB equations were recalculated from the external diameters in the range of 2-10 nm, the difference is explained in details in Ref. 48. A comparison of the isotherms is shown in Figure 2.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…(26), are not known. We have inspected the density data, based on grand canonical Monte Carlo simulation for another simple fluid, argon, in cylindrical silica pores, in which the fluid-fluid and solid-fluid interactions are represented by the Lennard-Jones potential [139]. The decrease in the mean density of the liquid with diminishing pore radius suggests a negative superficial excess of matter, aboutˆ BL I = −1.7 × 10 −6 mol/m 2 or −0.12 dense-packed atomic monolayers.…”
Section: Appendix: Derivation Of Eq (34)mentioning
confidence: 99%
“…One other relationship that was examined by Dobrzanski et al was how the elastic modulus depends on the size of the pores. Molecular simulation and DFT works [22,59,62], summarized in Sections II B, and IV, have shown that the bulk modulus of a subcritical fluid in confinement has a nearly linear relationship with reciprocal pore size, i.e., K ∝ 1/d. Eq.…”
Section: Local Elastic Propertiesmentioning
confidence: 99%